PERCEPTIONS OF TEACHERS RA AL HIJRAH BADRUL ULUM ON TEACHER CERTIFICATION POLICY IN IMPROVING THE QUALITY OF EDUCATION - Muhammad Rifa'i (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This paper aims to analyze teacher perceptions of teacher certification policies in improving the quality of education. The focus of the discussion of this study is how the teacher's perception of RA Al Hijrah Badrul Ulum regarding teacher certification policies in improving the quality of education. This research uses a qualitative approach with a case study method, while the data collection techniques used are participant observation, structured interviews and document analysis (documentation study). The results of this study indicate that the establishment of teacher certification policies helps teachers improve their skills and competencies as professionals, and helps from the welfare aspect that has been complained of by teachers. Even so, there are also bad effects that are commonly displayed by teachers, ranging from teaching only limited to fulfilling mandatory hours, to looking at certification from the aspect of welfare and lifestyle improvement.